Identifikasi Drug Related Problems (DRPs) pasien diabetes mellitus tipe 2 yang terkonfirmasi Covid-19 - Khaeditama Purnama Anwar; EM Sutrisna (Universitas Mataram, 2023)
Drug Related Problems (DRPs) are events or circumstances related to drug therapy that actually or have the potential to interfere with the desired therapeutic outcome. This study aims to identify the incidence of DRPs in patients with type 2 diabetes mellitus who are confirmed to have Covid-19. This research is a type of observational research with a cross sectional design. Data collection was carried out retrospectively by tracing patient medical record data. The number of patients who met the researcher’s inclusion criteria was 125 patients and on average each patient had DRPs. The categories of DRPs that occurred were indications without drugs for 57 patients (45,6%), drugs without indications for 11 patients (8,8%), inappropriate drug selection for 45 patients (36%), inadequate doses for 28 patients (22,4%), overdosage in 46 patients (36,8%), and drug interactions in 88 patients (70,4%)